Kajian Makna, Konsep, dan Teknologi Pembuatan Motif Batik Tradisional, Wilayah Barat, Provinsi Jawa Timur - ika ismurdyahwati; Atiqoh . (Universitas PGRI Adi Buana Surabaya, 2019)
This research looks for the basic pattern of meaning that traversesall the journey soft tribal history,through the 'old' batik motif, which originates from the western part of the East Java province.Through these mythologies, the position of man will be reflected in his cosmology and try to surveyhis life, be safe and happy according to his position in thisworld order. Its in terestis to document themotives to make inspiration for the developmen to fart in the future, with out putting aside theconcept soft its predecessors and the technology it uses. His research method, using qualitativeresearch, by optimizing observation and observation. Another goal ist okey now the extent to whichthese motives develop. In connection with the government program on the creative economy, it ispossible to develop the forms of motifs and functions of batik cloth that are not only used as clothfor the lower part of clothing, and kebaya (women) or beskap (men) as superiors. The resultsobtained in its development were, batik cloth with sacred motifs, became profane because of thelack of understanding of the concep to motives in the younger generation. Then in itsdevelopment,the batik cloths not only became profane but became material forother things to use, such as;negligee, casualpants, vacationclothes, hotel sandals, to formal clothes for uniforms andcelebrations.